The first gamma-ray bursts in the universe - Mesler, Robert Allan III; Whalen, Daniel J.; Smidt, Joseph; Fryer, Chris L.; Lloyd-Ronning, N. M.; Pihlström, Y. M. (The astrophysical journal, 2014)
Gamma-ray bursts (GRBs) are the ultimate cosmic lighthouses, capable of illuminating the universe at its earliest epochs. Could such events probe the properties of the first stars at z ∼ 20, the end of the cosmic Dark Ages? Previous studies of Population III (Pop III) GRBs only considered explosions in the diffuse relic H II regions of their progenitors or bursts that are far more energetic than those observed to date. However, the processes that produce GRBs at the highest redshifts likely reset their local environments, creating much more complicated structures than those in which relativistic jets have been modeled so far. These structures can greatly affect the luminosity of the afterglow and hence the redshift at which it can be detected. We have now simulated Pop III GRB afterglows in H II regions, winds, and dense shells ejected by the star during the processes that produce the burst. We find that GRBs with E iso, γ = 1051-1053 erg will be visible at z ≳ 20 to the next generation of near infrared and radio observatories. In many cases, the environment of the burst, and hence progenitor type, can be inferred from the afterglow light curve. Although some Pop III GRBs are visible to Swift and the Very Large Array now, the optimal strategy for their detection will be future missions like the proposed EXIST and JANUS missions with large survey areas and onboard X-ray and infrared telescopes that can track their near-infrared flux from the moment of the burst, thereby identifying their redshifts.
Gesehen am 18.08.2020